CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon
MyQuestionIcon
Question

(a) Complete the table and by inspection of the table, find the solution to the equation m + 10 = 16.

m

1

2

3

4

5

6

7

8

9

10

m + 10

(b) Complete the table and by inspection of the table, find the solution to the equation 5t = 35.

t

3

4

5

6

7

8

9

10

11

5t

(c) Complete the table and find the solution of the equation z/3 = 4 using the table.

z

8

9

10

11

12

13

14

15

16

...

3

(d) Complete the table and find the solution to the equation m − 7 = 3

m

5

6

7

8

9

10

11

12

13

m − 7

Open in App
Solution

(a) For m + 10, the table can be constructed as follows.

m

m + 10

1

1 + 10 = 11

2

2 + 10 = 12

3

3 + 10 = 13

4

4 + 10 = 14

5

5 + 10 = 15

6

6 + 10 = 16

7

7 + 10 = 17

8

8 + 10 = 18

9

9 + 10 = 19

10

10 + 10 = 20

By inspection, we can find that m = 6 is the solution of the above equation as for m = 6, m + 10 = 6 + 10 = 16

(b) For 5t, the table can be constructed as follows.

t

5t

3

5 × 3 = 15

4

5 × 4 = 20

5

5 × 5 = 25

6

5 × 6 = 30

7

5 × 7 = 35

8

5 × 8 = 40

9

5 × 9 = 45

10

5 × 10 = 50

11

5 ×11 = 55

By inspection, we can find that t = 7 is the solution of the above equation as for t = 7, 5t = 5 × 7 = 35

(c) For , the table can be constructed as follows.

z

8

9

10

11

12

13

14

15

16

By inspection, we can find that z = 12 is the solution of the above equation as for z = 12, = 4

(d) For m − 7, the table can be constructed as follows.

m

m − 7

5

5 − 7 = − 2

6

6 − 7 = − 1

7

7 − 7 = 0

8

8 − 7 = 1

9

9 − 7 = 2

10

10 − 7 = 3

11

11 − 7 = 4

12

12 − 7 = 5

13

13 − 7 = 6

By inspection, we can find that m = 10 is the solution of the above equation as for m = 10, m − 7 = 10 − 7 = 3


flag
Suggest Corrections
thumbs-up
0
BNAT
mid-banner-image